Practical consciousness for avoiding elderly loneliness: Study in Surabaya City, East Java - Amalia, Ayu Diah (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
Social change has an impact on changes within the family in terms of problems and needs. Modernization, industrialization, and urbanization create new problems for the elderly, such as reduced care and neglect due to the loss of the service provider role for the elderly. These conditions lead to elderly social degradation, and loneliness. This study aims to explore the experience of loneliness in the elderly and practical consciousness in managing loneliness. This qualitative research uses social phenomenology approach, and 19 elderly informants joined the research. The results showed that some elderly informants did not feel lonely despite living alone, but some elderly people also felt lonely although living with family. Practical consciousness of the elderly provides a good understanding as a strategy for how the elderly evaluate, and understand the social context around them and manage the loneliness experienced. Loneliness can reduce the well-being of the elderly, it takes the role of various parties such as family, community, and state to solve this problem. This study concludes that practical awareness in the elderly is one of the intervention strategies to avoid loneliness in the elderly.